"Don't Call Us Kushim": Racialized Experiences and Political Activism Among African Students in Israel in the 1960s. Issue 1 (2nd January 2022) - Lubotzky, Asher
ABSTRACT: During the 1960s, several hundreds of African students attended long-term academic or vocational programs in Israel. For Israel, offering higher education to Africans was considered a way to strengthen its influence in decolonizing Africa, while for African states, it was a means to gain vital technical expertise and reduce reliance on ex-colonial powers or the Cold War superpowers. African international students, however, were not merely pawns in this larger international political game. Responding to everyday racism and influenced by radical and Pan-Africanist ideas of the turbulent sixties, these students became active participants and commentators within Israeli society. They employed diverse strategies to promote anti-racist and anti-colonial causes, engaging in political activism at levels that were uncommon in the Israeli student social scene. By doing so, African students in Israel contested local prejudices about Africa and Africans and taught the hosting society important lessons on political awareness, broad-mindedness, acceptance, and racial tolerance. This history tells of understudied aspects of the global Black-Jewish relations in the 1960s. It also provides a novel perspective on Israeli society – one that surpasses the well-discussed Jewish-Arab or Ashkenazi-Mizrahi divisions – and contributes to the scholarly understanding of the meanings and manifestations of Blackness in Israel.